Color texture image retrieval based on Gaussian copula models of Gabor wavelets. (April 2017) - Li, Chaorong; Huang, Yuanyuan; Zhu, Lihong
Abstract: Color texture retrieval is a hot research area in image analysis. In this paper, we propose an efficient color texture retrieval method by using copula model based on Gabor wavelets. When Gabor wavelets are used to decompose color image, three types of dependence exist in the decomposed subbands of Gabor wavelets: color dependence, scale dependence and direction dependence. We analyze these dependencies and then capture them by using Gaussian copula function. Four copula schemes are developed, and accordingly four KLDs (Kullback-Leibler distances) of the copula schemes are introduced for color texture image retrieval. The evaluations of the proposed method are performed on several color texture databases including two large texture databases ALOT and STex. Experimental results demonstrate the proposed method has better performance than the state-of-the-art retrieval methods. Abstract : Highlights: We propose a color texture retrieval method by using Gabor wavelet and Copula model. We use copula model to capture the dependencies of Gabor wavelet and color channels. Four copula models are implemented based on Gabor wavelet in color space. Our method shows better performance on large databases than other popular methods.